511 Using 10-year injury trends in Western Australia to inform programs and policies. (20th November 2022) - Hendrie, De Delia; Randall, Sean; Lyle, Greg; Miller, Ted
Abstract : Understanding injury patterns is useful for injury surveillance, policy development and program evaluation. This study explores 10-year trends in injury incidence and costs in Western Australia and implications for policy and program development. Methods: Linked administrative health data including emergency department presentations, hospital admissions and deaths relating to injury in Western Australia was used to explore changes in the patterns of injury incidence and costs over a 10-year period to 2020. Descriptive and regression analysis was applied to examine statistically significant changes. Implications for policy and program development were explored with relevant stakeholders including in government, non-government organisations and consumer groups. Results: Falls remained the most common mechanism of unintentional injury, followed by inanimate mechanical forces and transport crashes. Patterns of injury rates by age group and gender reflected past distributions, with higher rates for males and older people. Socio-economic determinants significantly impacted injury rates. An increase in occurrence of injury over the 10-year period were disrupted by the COVID-19 lockdown, with mechanisms varying for some injury types. Consultation with stakeholders highlighted gaps in existing policies and programs and potential interventions were proposed. Conclusion: Cross-sectional and trend analysis of injury patterns provides an evidence base to guide targeted based approaches to injury prevention to reduce disparities in injury rates. Socio-economic inequalities remain a public health concern.